Effect of viscosity on swimming by the lateral and polar flagella of Vibrio alginolyticus. - Atsumi, T (1996)
By using mutants of Vibrio alginolyticus with only a polar flagellum (Pof+ Laf-) or only lateral flagella (Pof- Laf+), we examined the relationship between swimming speed and the viscosity of the medium for each flagellar system. Pof+ Laf- cells could not swim in the high-viscosity environment (ca. 200 cP) in which Pof- Laf+ cells swam at 20 microns/s. The Pof- Laf+ cells swam at about 20 microns/s at normal viscosity (1 cP) without the viscous agent, and the speed increased to 40 microns/s at about 5 cP and then decreased gradually as the viscosity was increased further. These results show the functional difference between polar and lateral flagella in viscous environments.